A Formal Model for the Cultural Evolutionary Dynamics of Counterintuitive Cultural Messages. (4th May 2020) - Salazar, Carles
Abstract : In this article I present a formal model for the cultural evolution of counterintuitive cultural messages, specifically, religious ideas. This model tries to account for the reproduction of counterintuitive religious ideas by introducing a new parameter: the means of cultural communication by which those ideas are transmitted. Means of cultural communication can be classified alongside a continuum that goes from the cognitively optimal to the cognitively costly. Very simple intuitive messages may replicate weakly if they are transmitted through cognitively costly means of communication, and conversely, highly counterintuitive messages will reproduce without difficulty if they are transmitted through cognitively optimal means of communication. The formal model I propose in this study is based on a new version of the model put forward by Joseph Henrich to account for the Tasmanian case of cultural loss.